THE INFLUENCE OF LEADERSHIP STYLE, JOB SATISFACTION AND ORGANIZATIONAL JUSTICE ON COUNTERPRODUCTIVE WORK BEHAVIOR IN EMPLOYEES PDAM IE BEUSAREE RATA LHOKSEUMAWE CITY - Hanny Rahmatunnisa; Sullaida; Ibrahim Qamarius; Khairawati; Nurmala (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This research aims to determine the influence of leadership style, job satisfaction and organizational justice on counterproductive work behavior among employees of PDAM Ie Beusaree Rata, Lhokseumawe City. This type of research is descriptive quantitative research. Where the data used in this research is primary data. The population in this study were employees who worked at PDAM Ie Beusaree Rata, Lhokseumawe City. This research used a saturated sampling method by distributing questionnaires to the entire population of 35 people. The variable measurement scale used in this research is the Likert scale. Data analysis in the research used IBM SPSS version 26 with a data analysis method using multiple linear regression consisting of data instrument testing, classical assumption testing and hypothesis testing. The results of the research show that leadership style, job satisfaction and organizational justice have a negative and significant effect on counterproductive work behavior among employees of PDAM Ie Beusaree Rata, Lhokseumawe City. This means that if the leadership style, job satisfaction and organizational justice in the company decrease, it can trigger counterproductive work behavior in employees. So company management needs to improve leadership style, job satisfaction and organizational justice to minimize employee counterproductive work behavior by improving the indicators used in this research.